Ancient households on the north coast of Peru - Johnson, Ilana; Pacifico, David; Cutright, Robyn E. (University Press of Colorado, 2021)
"Not limited to one time period or civilization, provides insight into the development of complex, urban, and state-level society in the region, showing how observed domestic patterns inform a new archaeological perspective on general processes in domestic life in and beyond Andean prehistory."--